Sinc-Fractional Operator on Shannon Wavelet Space - Cattani, Carlo (Frontiers in Physics, 2018)
In this paper the sinc-fractional derivative is extended to the Hilbert space based on Shannon wavelets. Some new fractional operators based on wavelets are defined. One of the main task is to investigate the localization and compression properties of wavelets when dealing with the non-integer order of a differential operator.